Airway epithelial ITGB4 deficiency in early life mediates pulmonary spontaneous inflammation and enhanced allergic immune response. Issue 5 (22nd January 2020) - Tang, Sha; Du, Xizi; Yuan, Lin; Xiao, Gelei; Wu, Mengping; Wang, Leyuan; Wu, ShuangYan; Duan, Zhen; Xiang, Yang; Qu, Xiangping; Liu, Huijun; Zou, Yizhou; et al.
Abstract: Lung immune responses to respiratory pathogens and allergens are initiated in early life which will further influence the later onset of asthma. The airway epithelia form the first mechanical physical barrier to allergic stimuli and environmental pollutants, which is also the key regulator in the initiation and development of lung immune response. However, the epithelial regulation mechanisms of early‐life lung immune responses are far from clear. Our previous study found that integrin β4 (ITGB4) is decreased in the airway epithelium of asthma patients with specific variant site. ITGB4 deficiency in adult mice aggravated the lung Th2 immune responses and enhanced airway hyper‐responsiveness (AHR) with a house dust mite (HDM)‐induced asthma model. However, the contribution of ITGB4 to the postnatal lung immune response is still obscure. Here, we further demonstrated that ITGB4 deficiency following birth mediates spontaneous lung inflammation with ILC2 activation and increased infiltration of eosinophils and lymphocytes. Moreover, ITGB4 deficiency regulated thymic stromal lymphopoietin (TSLP) production in airway epithelial cells through EGFR pathways. Neutralization of TSLP inhibited the spontaneous inflammation significantly in ITGB4‐deficient mice. Furthermore, we also found that ITGB4 deficiency led to exaggerated lung allergic inflammation response to HDM stress. In all, these findings indicate that ITGB4 deficiency in early life causes spontaneous lung inflammation and induces exaggerated lung inflammation response to HDM aeroallergen.